The Liberal Political Realism of Bernard Williams - Annamária Csornay (Elpis)
Bernard Williams’s “Realism and Moralism in Political Theory” is without question one of the central texts of liberal political realism. The success of the text is due to its influential critique of dominant liberal approaches – primarily that of John Rawls –, and in its distinct approach to the grounding of liberalism itself. Even though Williams’s text had a great impact on contemporary political theory, understanding its philosophical foundations is unfairly neglected in academic discourse. The aim of this paper is to show the fundamental view behind Williams’s rejection of moralism that dominates political thinking. The strength of Williams’s approach is that it makes it clear that rationality has a limited authority in morality as well as in politics, and that it redefines the relation between morality and politics. Williams’s view has its own set of challenges, which come forward expressly in his account of legitimacy. Nevertheless, Williams’s realist arguments are indeed compelling for contemporary theorists.